2016
DOI: 10.1039/c6ra17284a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide polypiperazine-amide nanofiltration membrane for improving flux and anti-fouling in water purification

Abstract: In this study, a facile polypiperazine-amide (PPA) composite nanofiltration (NF) membrane with nanomaterial graphene oxide (GO) incorporated into a polyamide (PA) layer for high water flux and anti-fouling was fabricated by interfacial polymerization (IP). The chemical composition, structure and surface properties of the fabricated PPA/GO and PPA composite NF membranes were characterized by FTIR, XPS, FE-SEM, AFM, zeta-potential and contact angle measurements. The separation properties and anti-fouling ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 67 publications
2
25
0
1
Order By: Relevance
“…[8][9][10][11] The focus has, indeed, moved on to layered adsorption membranes made of nanoscaled adsorbents as zeolites, MOFs, graphene oxide and other compounds. [12][13][14][15][16][17][18][19] Considering, for example, nanocellulose based materials, inspired by the concept of thin-lm nanocomposites, both Cao et al 20 and Ma et al 9 introduced into the membranes thin TOCNF layers by casting and impregnating electrospun mats, which were prepared and characterized for ultraltration with pore sizes in the 10-100 nm range. 9,20 TEMPO-oxidised cellulose nanobers (TOCNF) have been established as highly functional and biobased adsorbents for water purication due to their high specic surface area, abundant functionality, high strength and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The focus has, indeed, moved on to layered adsorption membranes made of nanoscaled adsorbents as zeolites, MOFs, graphene oxide and other compounds. [12][13][14][15][16][17][18][19] Considering, for example, nanocellulose based materials, inspired by the concept of thin-lm nanocomposites, both Cao et al 20 and Ma et al 9 introduced into the membranes thin TOCNF layers by casting and impregnating electrospun mats, which were prepared and characterized for ultraltration with pore sizes in the 10-100 nm range. 9,20 TEMPO-oxidised cellulose nanobers (TOCNF) have been established as highly functional and biobased adsorbents for water purication due to their high specic surface area, abundant functionality, high strength and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…The route (I) is oen preferred because GO demonstrates better dispersibility in aqueous solution than in organic phase. 9,[24][25][26] Lai et al 8 and Wang et al 27 investigated the effect of GO concentration in an aqueous PIP solution on membrane performance and found that TFN NF membrane with embedding an appropriate amount of GO exhibited better membrane performance owing to the remarkable increase in membrane hydrophilicity and surface negativity. Bano et al 28 and Xia et al 29 studied the effect of the GO concentration in an aqueous MPD solution on membrane performance and showed that GO-embedded TFN NF membranes offered higher water uxes and better antifouling properties.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the concentration of TiO 2 from 0.01 to 0.2% may have confined the diffusion of PIP slowing growth of the nodular structures . Therefore, linkage between monomers used to form the PA layer may be stronger in TFN 0.01 and TFN 0.05 membranes than in TFN 0.2 membranes …”
Section: Resultsmentioning
confidence: 99%